Optimizing Electrical Performance in PV Hydroponic Systems Through Automated Pump Control and TDS-Based IoT Monitoring - Rafian, Zarif; Zahurul, syed (Evolution in Electrical and Electronic Engineering, 2023)
This project aims to develop an IoT-based automated control system for a photovoltaic hydroponic system, integrating sensor-based nutrient delivery, energy-efficient pump control, and real-time monitoring. The objectives include designing an automated pump control system, implementing an IoT monitoring system for real-time data collection, and evaluating the optimization of electrical energy usage. Key findings indicate significant energy savings achieved by the automated pump control system, resulting in reduced energy consumption and a more sustainable approach to hydroponic cultivation.